MYB elongation is regulated by the nucleic acid binding of NFekB p50 to the intronic stem-loop region - Pereira, L.; Hugo, H.; Malaterre, J.; Huiling, X.; Sonza, S.; Cures, A.; Purcell, D.; Ramsland, Paul; Gerondakis, S.; Gonda, T.; Ramsay, R. (Public Library of Science, 2015)
MYB transcriptional elongation is regulated by an attenuator sequence within intron 1 that has been proposed to encode a RNA stem loop (SLR) followed by a polyU tract. We report that NFekBp50 can bind the SLR polyU RNA and promote MYB transcriptional elongation together with NFekBp65. We identified a conserved lysine-rich motif within the Rel homology domain (RHD) of NFekBp50, mutation of which abrogated the interaction of NFekBp50 with the SLR polyU and impaired NFekBp50 mediated MYB elongation. We observed that the TAR RNA-binding region of Tat is homologous to the NFekBp50 RHD lysine-rich motif, a finding consistent with HIV Tat acting as an effector of MYB transcriptional elongation in an SLR dependent manner. Furthermore, we identify the DNA binding activity of NFekBp50 as a key component required for the SLR polyU mediated regulation of MYB. Collectively these results suggest that the MYB SLR polyU provides a platform for proteins to regulate MYB and reveals novel nucleic acid binding properties of NFekBp50 required for MYB regulation.